Pengaruh Latihan Plyometric Terhadap Power Otot Tungkai Atlet Bola Voli Kenzie - Andre Febrian; Sukardi Sukardi; Putri Cicilia kristina (CV. Ulil Albab Corp, 2026)
This study aims to determine the effect of drill training on the improvement of smash abilities in athletes of the KENZIE volleyball club. The population in this study consisted of 35 male volleyball athletes. The sampling technique used purposive sampling, resulting in 15 athletes aged 13 to 18 years as research respondents. The method used was an experiment with a one-group pretest-posttest design to observe changes in abilities before and after treatment. Data collection was conducted through the VERTICAL JUMP TEST INSTRUMENT DEVELOPED BY (WIDIASTUTI 2015:109), while data analysis techniques included normality testing using the Shapiro-Wilk test and hypothesis testing using a paired sample t-test. The data analysis results show a t-test value of 11.500, greater than the table t value of 2.145 (df = 14, N = 15). The average pretest score is 256 and the posttest shows an increase of 18.2 or 7.11%. These results indicate an improvement in smash ability after being given plyometric training. Since t_calculated > t_table, H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that drill training affects the improvement of jump height ability in Kenzie volleyball club athletes and can be used as one of the effective training methods to enhance athlete performance.